Size Distribution of Ambient Particulate Matter and Its Constituent Chemical Species Involving Saccharides During Early Summer in a Chinese Megacity - Khan, Jahan Zeb; Sun, Long; Tian, Yingze; Dai, Qili; Hu, Tongxin; Feng, Yinchang (Frontiers in Environmental Science, 2021)
The ambient particulate matter (PM) pollution adversely influences the human health and natural environment. The size distribution of ambient PM determines the physiochemical and optical properties of ambient aerosol, whereas it reflects the variability in local and regional PM emission sources and formation mechanisms. In the present work, the size distribution and characteristics of the carbonaceous, ionic, elemental, and saccharide species were categorically investigated for the fraction-wise PM in Tianjin during 2018 early summer. The average concentrations were 32.4, 20.9, and 49.3 μg/m3 for the PM1, PM1–2.5, and PM2.5–10, respectively. The coarse PM2.5–10 accounted for most of the PM10 mass (47%), followed by the fine PM1 (33%) and intermodal PM1–2.5 (20%). The carbonaceous and ionic species exhibited bimodal distribution and were distributed mostly to the fine size fraction and then to the coarse size fraction. The elemental species exhibited unimodal distribution and were distributed mostly to the coarse size fraction. The specific saccharide species indicated the significant contribution of biomass burning and primary biogenic emissions. The bimodal mass size distribution of levoglucosan indicated the significant biomass burning contributions to the fine and coarse size fractions. The unimodal glucose, fructose, and arabitol distribution and the bimodal mannitol distribution indicated the dominant primary biogenic contributions to the coarse size fraction. The PM1/PM10, PM1–2.5/PM10, PM2.5–10/PM10, OC/EC, SOC/OC, AE/CE, NO3–/SO42–, K+/EC, and levoglucosan/K+ ratios were used to investigate the characteristics of the ambient size-fractionated PM. The anthropogenic sources (combustion processes, traffic emissions, and secondary particles, etc.) contributed mostly to the fine PM1 and intermodal PM1–2.5 fractions, whereas the natural sources (primary biogenic, marine salt, and mineral dust, etc.) contributed mostly to the coarse PM2.5–10 fraction. This work is a significant addition to the multi-size ambient PM’s size distribution and characterization studies.